2008
DOI: 10.1109/tbme.2007.899347
|View full text |Cite
|
Sign up to set email alerts
|

Validation of High Gradient Magnetic Field Based Drug Delivery to Magnetizable Implants Under Flow

Abstract: The drug-eluting stent's increasingly frequent occurrence late stage thrombosis have created a need for new strategies for intervention in coronary artery disease. This paper demonstrates further development of our minimally invasive, targeted drug delivery system that uses induced magnetism to administer repeatable and patient specific dosages of therapeutic agents to specific sites in the human body. Our first aim is the use of magnetizable stents for the prevention and treatment of coronary restenosis; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 21 publications
1
52
1
Order By: Relevance
“…Recent in vitro [37][38][39] and in vivo [40,41] studies of a stent-based system further demonstrated the feasibility of this IA-MDT technique. However, none of the theoretical works have been validated with any in vitro experimental data; nor have the in vitro and in vivo experimental studies been compared with any model predictions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent in vitro [37][38][39] and in vivo [40,41] studies of a stent-based system further demonstrated the feasibility of this IA-MDT technique. However, none of the theoretical works have been validated with any in vitro experimental data; nor have the in vitro and in vivo experimental studies been compared with any model predictions.…”
Section: Introductionmentioning
confidence: 92%
“…Hence, the magnetic force becomes significantly diminished as the depth of the target site increases, making sites that are more than a few centimeters deep in the body difficult to target. Nevertheless, some recent research on the MDT approach has shown that these two limitations can be circumvented by simply using a ferromagnetic implant, such as a wire or seed, in conjunction with the MDCPs and the external magnetic field source [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. This new MDT approach is referred to as implant assisted (IA)-MDT.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed one way to locally create a high-gradient magnetic field that is to implant ferromagnetic needles or stents to the target site. The way had been proved to be effective for magnetic drug targeting in-vitro and the theory was demonstrated [21][22][23][24]. Fig.…”
Section: Design Of Magnetic Implanting Systemmentioning
confidence: 99%
“…However, due to the short range of the magnetic force and the adverse effect of the hydrodynamic force, the progress of this approach has been stalled for more than three decades, leaving potential applications looming. Fortunately, the use of a magnetic implant to augment the magnetic force imparted by the external magnet has recently brought new light to MDT [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The net effect is that the collection of the MDCPs at the desired site is greatly increased by the presence of this ferromagnetic implant compared to just using the external magnet alone. Several enlightening theoretical [4][5][6][7][8][9][10][11][12], experimental [11][12][13][14][15], and animal model [16,17] studies have been carried out recently using wires, stents, and even seeds as the implant for IA-MDT.…”
Section: Introductionmentioning
confidence: 99%